Cerebral Venous Sinus Thrombosis With Hereditary Antithrombin Iii Deficiency After COVID-19 Vaccination: A Case Report - Sayeed, SK Jakaria Been; Mahmud, Reaz; Rahman, Sabrina; Moniruzzaman, Md; Kabir, AKM Humayon; Biswas, Prodip Kumar; Yousuf, Mohammad Abdullah (Journal of Dhaka Medical College, 2023)
Hereditary antithrombin III deficiency is a prothrombotic disorder with an associated 50-90% risk of venous thrombosis. It rarely causes cerebral venous thrombosis in adults. Variable clinical presentations make the diagnosis a challenge. Careful clinical history, extensive clinical examinations, comprehensive investigations, and prompt management are necessary to save lives. COVID-19 vaccine-induced immune thrombotic thrombocytopenia may be a risk factor for cerebral venous thrombosis in these cases. Here, we are reporting an adult female with cerebral venous sinus thrombosis after receiving the COVID-19 vaccine. Subsequently, she was diagnosed with hereditary antithrombin III deficiency. J Dhaka Med Coll. 2021; 30(2) : 227-231